A representação metafórica da imigração e do refúgio na mídia: um estudo comparativo entre os jornais Folha de São Paulo e The New York Times durante os períodos eleitorais de 2020 e 2022 - Igor Alexsander Pereira (2024)
The present study seeks to investigate the metaphorical representations of immigration and refuge in traditional Brazilian and North American media. The focus of the work is to verify the way in which the subject is addressed in the media of both countries, with emphasis on their last electoral campaign periods (2020 in the United States and 2022 in Brazil). The study aims to understand the differences and similarities in the approach to the theme in this specific period. This analysis was carried out in the light of Cognitive Linguistics, based mainly on the seminal work for the study of metaphors, Lakoff and Johnson (1980), in the book Metaphors we live by. As this is a comparative analysis, we also rely on Kövecses (2005), who states that the metaphor can vary between different cultures and also within the same culture, being motivated, for example, by the determinations of different contexts. We will also rely on Thibodeau and Boroditsky (2011) who attest, through their experiments, the influence of metaphorical representations on reasoning and decision-making, and how this influence is not clear to people is also an important groundwork. Due to the focus on the electoral context, exploring the ideological character of metaphors, the work draws on authors such as Goatly (2007), Musolff (2016a), and Charteris-Black (2004), who contribute to the analysis of political speeches. In order to carry out the analysis, news were collected from the online versions of important and widely circulated newspapers in both countries, The New York Times in the United States, and Folha de São Paulo, in Brazil. The news refers to the years 2020 and 2022, which is the period between the last two electoral races in the two countries. The collection and analysis were carried out using Sketch Engine, a corpus linguistics tool that will allow the analysis of lines of agreement to identify metaphorical occurrences, identified and categorized using the methodology of Stefanowitsch (2006). Metaphor identification was performed using a combination of methods, including the Metaphor Identification Procedure (MIP) and the Metaphor Identification Procedure – Vrije Universiteit (MIPVU). The results show a scenario that confirms previous works, displaying many similarities in the use of metaphors by the two newspapers and differences that are understandable based on the cultural analysis of the two societies and how this culture is transcribed in the media. For example, among the results of the American newspaper, attention is drawn to the high incidence of the source-domain WAR, which highlights an increase in associations of the immigration process as a war being fought, mainly due to Donald Trump's speeches. On the other hand, has a greater incidence of source-domains linked to LIQUID, NATURAL PHENOMENON and CRISIS, highlighting an image that is also negative but not so directly combative.